Comparative analysis of street art cataloguing projects in the cities of Monterrey (Mexico) and Jaen (Spain): Proposal for the inclusion of communities - Luque Rodrigo, Laura; Díaz Fernández, Adris; Moral Ruiz, Carmen (Street Art & Urban Creativity, 2021)
In the last few months of 2020 and the first half of 2021, two street art cataloguing projects have been carried out in two cities in different countries that have made it possible to put methodological proposals into practice that until now have remained mainly at a theoretical level. This is the project "Painted on the wall. Study of wall painting in the province of Jaen in the XX-XXI centuries; financed by the Institute of “Giennense” Studies (Provincial Government of Jaen) and the project;The commissioned street art murals creation of the cultural-artistic Festival of Urban Expressions CALLEGENERA " in the city of Monterrey, financed by the Mexican Programme for the Promotion of Cultural Projects and Co-investments. In these projects, methodological systems for working and collecting information, cataloguing cards and models for interviewing different artists have been developed, with a common theoretical basis, such as the proposals that emerged within the GEIIC Street Art and Commissioned Street Art Murals Group, and taking into account the proposals of the CAPuS project and YOCOCU. For this reason, this paper analyses both projects in terms of their methods and results, and draws conclusions about which options have worked best from the perspective of optimising resources for future projects. A proposal is also made to improve the street art cataloguing cards by including information about the correlation between the work and the communities surrounding it, since street art only makes sense in its context, and some of this information is lost when the cards are made. Furthermore, from the perspective of taking possible action for the preservation of the artwork, a relationship with the communities in which they are integrated is fundamental.